1994
DOI: 10.1111/j.1432-2277.1994.tb01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of non-parenchymal liver cells in ischaemia-reperfusion liver injury: protective effects of muramyl dipeptide

Abstract: It has been suggested that non-parenchymal liver cells play a central role after ischaemia and reperfusion of the liver. Male Lewis rats were subjected to 90 min of warm liver ischaemia. Four groups were constituted: group 1, no treatment; group 2, muramyl dipeptide treatment, activation of Kupffer cells; group 3, dextran sulphate injection, Kupffer cell blockade; and group 4, gadolinium chloride administration, Kupffer cell blockade. Dextran sulphate (4 mg/100 g) and gadolinium chloride (GdCl2, 0.7 mg/100 g) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
(4 reference statements)
1
10
0
Order By: Relevance
“…Several studies have shown that Kupffer cells in the cold-stored liver appear to be activated [3,5,6] and that inhibition of Kupffer cell function contributes to the prevention of reperfusion injury [5,27]. Pathomechanisms associated with warm I/R, as in our experimental model, seem to differ from those after cold I/R in liver transplantation, since increased phagocytic activity of KCs was reported after cold storage, transplantation, and reperfusion of rat liver [7], and since reduced phagocytic activity of Kupffer cells was reported after warm liver I/R [11][12][13][14]. Depression of the phagocytic activity of Kupffer cells may have important consequences for postischemic liver viability [13,15] and may contribute to systemic endotoxinemia and death [28,29].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Several studies have shown that Kupffer cells in the cold-stored liver appear to be activated [3,5,6] and that inhibition of Kupffer cell function contributes to the prevention of reperfusion injury [5,27]. Pathomechanisms associated with warm I/R, as in our experimental model, seem to differ from those after cold I/R in liver transplantation, since increased phagocytic activity of KCs was reported after cold storage, transplantation, and reperfusion of rat liver [7], and since reduced phagocytic activity of Kupffer cells was reported after warm liver I/R [11][12][13][14]. Depression of the phagocytic activity of Kupffer cells may have important consequences for postischemic liver viability [13,15] and may contribute to systemic endotoxinemia and death [28,29].…”
Section: Discussionmentioning
confidence: 86%
“…In hypothermic I/R, activation of Kupffer cells is responsible for a massive release of monokines such as tumor necrosis factor ␣ (TNF-␣) and interleukin-1 (IL-1) [4,5] and an increase in phagocytic activity [6,7]. In normothermic I/R, several studies [8 -10] have demonstrated a massive release of TNF-␣, whereas phagocytic activity of KCs was decreased [11][12][13][14], which might contribute to systemic endotoxemia and death. Several studies have shown that modulation of macrophage activity may modify hepatic injuries after I/R [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,12,13 In addition, activated Kupffer cells may release eicosanoids and monokines (IL-1, IL-6, TNF-␣, TNF-␤). 14,15 In hepatocytes, reoxygenation may trigger a mitochondrial respiratory chain-dependent production of OFR, 3,16 which requires molecular oxygen and NADPH to generate O 2 .Ϫ anions. 3,10,11 These OFR could be involved in apoptosis, which leads to postoperative dysfunction and even to graft rejection.…”
mentioning
confidence: 99%
“…Literature on the transplantation of nonparenchymal cell fractions is scarce, but a positive influence of nonparenchymal cells in coculture systems with hepatocytes has been described [Miyazawa et al, 2005]. Additionally, stellate cells, sinusoidal endothelial cells and Kupffer cells are known to influence the proliferation of hepatocytes [Malik et al, 2002] and seem to positively influence oval cell-driven hepatic regeneration [Gugenheim and Crafa, 1994;Zhang et al, 2009]. When reducing immunosuppression later on, the transplanted cells would have the clear advantage of being syngeneic to the organ recipient.…”
Section: Discussionmentioning
confidence: 99%